أصول النحو عند البصريين : دراسة إبستيمولوجية - M. Dzikrul Hakim Al Ghozali (Fakultas Syariah dan Adab Universitas Nahdlatul Ulama Sunan Giri, 2020)
“Explaining the grammar principles is a explain of the basic sources from which its phenomena were taken and its rulings are extrapolated from it, and it is unavoidable for every Arab grammar student to stand on it and consider it. The grammarians of Basrien were the first to reexplain these principles and stick to them. They have their own grammatical method and they infer this evidence. The Basroun relies on hearing such as the Qur’anic verses, the hadiths of the Prophet and the words of the Arabs like the Kufic, but they require many conditions, especially in the hadith and the words of the Arabs, as well as by analogy and consensus.”